Elimination of Cancer Stem-Like "Side Population" Cells in Hepatoma Cell Lines by Chinese Herbal Mixture "Tien-Hsien Liquid". (14th October 2012) - Yao, Chih-Jung; Yeh, Chi-Tai; Lee, Liang-Ming; Chuang, Shuang-En; Yeh, Chuan-Feng; Chao, Wan-Ju; Lai, Tung-Yuan; Lai, Gi-Ming
Abstract : There are increasing pieces of evidence suggesting that the recurrence of cancer may result from a small subpopulation of cancer stem cells, which are resistant to the conventional chemotherapy and radiotherapy. We investigated the effects of Chinese herbal mixture Tien-Hsien Liquid (THL) on the cancer stem-like side population (SP) cells isolated from human hepatoma cells. After sorting and subsequent culture, the SP cells from Huh7 hepatoma cells appear to have higher clonogenicity and mRNA expressions of stemness genes such as SMO, ABCG2, CD133, β - catenin, and Oct-4 than those of non-SP cells. At dose of 2 mg/mL, THL reduced the proportion of SP cells in HepG2, Hep3B, and Huh7 cells from 1.33% to 0.49%, 1.55% to 0.43%, and 1.69% to 0.27%, respectively. The viability and colony formation of Huh7 SP cells were effectively suppressed by THL dose-dependently, accompanied with the inhibition of stemness genes, e.g., ABCG2, CD133, and SMO . The tumorigenicity of THL-treated Huh7 SP cells in NOD/SCID mice was also diminished. Moreover, combination with THL could synergize the effect of doxorubicin against Huh7 SP cells. Our data indicate that THL may act as a cancer stem cell targeting therapeutics and be regarded as complementary and integrative medicine in the treatment of hepatoma.